Electric Utility Plant Replacement Costs. - Livingstone, John Leslie (The Accounting Review, 1967)
Abstract This article focuses on the issue of use of current prices in financial statements by accountants. Most of the discussion over the use of current prices versus historical costs has been at a theoretical level, and relatively few studies have been published on the practical implementation and use of current price valuation. Since generally accepted accounting principles do not include price adjustments in the primary financial statements, it is not surprising that practical examples of price adjustments are seldom seen. In the valuation of the net utility plant, price adjustments are made by some regulatory agencies. The alternative rate base evaluation methods in general use are, original cost, the historical dollar cost of utility plant when first put into public service. Reproduction cost, the dollar cost at current prices of reproducing the existing depreciation. Fair value, a composite of original cost and reproduction cost. Thus, reproduction cost method and fair value method take into account current prices.